(untitled) (American Journal of Islam and Society, 2004)
Have the tragic events of 9/11 resulted in a profound change in the interactions between the Muslim world and the West, or has the carnage simply accelerated an already present trend of strained relations? It is too early to know, but when historians begin looking back, they will likely find evidence to support both assertions. With the introduction of the USA PATRIOT Act, which allows the government unprecedented opportunities to spy on people, greatly infringing upon their civil liberties, the treatment of the detainees at Guantanamo Bay, racial profiling, and the harassment and deportation of Muslims residing in the country, the Bush administration appears to be leading the “free world” into a new variant of right-wing authoritarian government. On the other hand, the American occupation of Iraq and the Bush administration’s plans to reshape the Middle East bear an uncanny resemblance to a policy paper published in 1996 by an Israeli think-tank, the Institute for Advanced Strategic and Political Studies: “A Clear Break: A New Strategy for Securing the Realm.” Of course the symmetry between the 1996 proposals (i.e., remove Saddam Hussein and weaken Syria and Iran) and the current policies are no surprise, since three of the eight coauthors now hold key Bush administration positions: Richard Perle, member of the Pentagon’s Defense Policy Board; Douglas Feith, undersecretary of defense for policy; and David Wurmser, Vice President Dick Cheney’s Middle East advisor. Thus, 9/11 has simply given the neo-conservatives an excuse and the ability to execute what had already been envisaged. The Middle East, long under colonial subjugation, is re-experiencing western aims to dominate, control, and reshape it. Thus, from a Muslim perspective, 9/11 appears to have confirmed, with a vengeance, global power structures instead of ushering in a new era. In Covering Islam, published by the late Edward Said in 1981, Said observed: “For almost every Muslim, the mere assertion of an Islamic identity becomes an act of nearly cosmic defiance and a necessity for survival (p. 72).” Though written more than 20 years ago, how more true is this observation now? Even the simple act of naming a child (especially boys) is fraught with difficulties. Many of the best-loved Muslim names, ...